STUDENTS’ DIFFICULTIES IN WRITING DESCRIPTIVE TEXT - Duha, Merliana (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
Writing is one of important skills in English, including writing descriptive text. However, there are still many students who get difficulties in writing descriptive text. This research aimed to find out the students’ difficulties and causes of the students’ difficulties in writing descriptive text at eighth grade of SMP Negeri 2 Telukdalam. This research used qualitative method. The data were collected by documentation, interview, and observation. The result of data analysis showed that: (1) the students’ difficulties in writing descriptive text consist of difficulties in generic features, textual language, syntactical language, spelling, and other students’ difficulties in writing descriptive text: capitalization, finding and organizing ideas; (2) the causes of the students’ difficulties in writing descriptive text were because of psychological problems: less motivation, less practice of writing, less interested in learning English, less confidence, and having poor thought that English and writing difficult; linguistic problems: lack of grammar and vocabulary mastery; and cognitive problems: lack of background knowledge of capitalization, punctuation, and spelling; moreover, less media of learning was also one of the causes of the students’ difficulties in writing descriptive text. Based on the finding, it is concluded that the students at the eighth grade of SMP Negeri 2 Telukdalam have difficulties in writing descriptive text. It is suggested that writing descriptive text should be learned and taught intensively.